Advances in the Application of Biomimetic Endometrium Interfaces for Uterine Bioengineering in Female Infertility - Han, Qixin; Du, Yanzhi (Frontiers in Bioengineering and Biotechnology, 2020)
The Asherman’s syndrome, also known as intrauterine adhesion, often follows endometrium injuries resulting from dilation and curettage, hysteroscopic resection, and myomectomy as well as infection. It often leads to scarring formation and female infertility. Pathological changes mainly include gland atrophy, lack of vascular stromal tissues and hypoxia and anemia microenvironment in the adhesion areas. Surgical intervention, hormone therapy and intrauterine device implantation are the present clinical treatments for Asherman’s syndrome. However, they do not result in functional endometrium recovery or pregnancy rate improvement. Instead, an increasing number of researches have paid attention to the reconstruction of biomimetic endometrium interfaces with advanced tissue engineering technology in recent decades. From micro-scale cell sheet engineering and cell-seeded biological scaffolds to nano-scale extracellular vesicles and bioactive molecule delivery, biomimetic endometrium interfaces not only recreate physiological multi-layered structures but also restore an appropriate nutritional microenvironment by increasing vascularization and reducing immune responses. This review comprehensively discusses the advances in the application of novel biocompatible functionalized endometrium interface scaffolds for uterine tissue regeneration in female infertility.